Personalization of Content in Video-on-Demand Services: Insights from Satisfaction over Social Media Algorithms - Alicia Urgellés-Molina, PhD.; Mónica Herrero, PhD. (Comhumanitas)
The rapid evolution of algorithmic personalization has reshaped user experiences on social media and video-on-demand (VOD) platforms, tailoring content recommendations to individual preferences. This paper explores the intersection of user satisfaction, algorithmic responsiveness, and consumption patterns, emphasizing the influence of AI-driven recommendations. It highlights how perceptions of algorithmic customization impact user behavior, fostering both engagement and concerns over echo chambers and privacy.